Gelling pectins from carrot leftovers extracted by industrial-enzymes with ultrasound pretreatment - Perez, Carolina Daiana; Idrovo Encalada, Alondra Mariela; Gerschenson, Lia Noemi; Rojas, Ana Maria; Fissore, Eliana Noemi (Elsevier, 2019)
Misshapen carrots were upgraded as orange-colored pectin-enriched fractions (PEFs) useful as gelling agents and containing α- and β-carotenes, lutein, and α-tocopherol, by applying a green process consisting of an ultrasound (US) pretreatment (12.27 W/cm2 power intensity) followed by stirring in citrate buffer (pH 5.20) either without or with an industrial enzyme (fungal and bacterial hemicellulases, and cellulase) commercialized as baking improvers. PEFs showed uronic acid (UA) contents between 39 and 51% with low degree of methylesterification (DM, 37.2–48%), 11–22% degree of acetylation (DA), and a common molecular weight of 121,000–138,000 Da. The protein contents were 9.6–17.8%. Only the use of fungal hemicellulase produced per se higher yield of the PEF obtained (10.4%), in comparison to the non-US pretreated citrate buffer extracted pectins (6.9%). The US-pretreatment was the step that decisively produced high extractive yields (≈20%), while there was not additional contribution of industrial enzymes. However, enzymes permitted to obtain PEFs with different gel characteristics. US-pretreated PEFs at 2.00% w/v in water showed the best rheological performances, forming calcium-crosslinked true gels, more structured and with higher elastic (G’) modulus than non-US pretreated isolated fractions, one of which did not gel, being then useful as functional additives for food formulation.